2018
DOI: 10.1111/jopy.12430
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in emotion regulation goals: Does personality predict the reasons why people regulate their emotions?

Abstract: Objective We investigated how the Big Five traits predict individual differences in five theoretically important emotion regulation goals that are commonly pursued—pro‐hedonic, contra‐hedonic, performance, pro‐social, and impression management. Method We conducted two studies: (a) a large survey study consisting of undergraduates (N = 394; 18–25 years; 69% female; 56% European American) and community adults (N = 302; 19–74 years; 50% female; 75% European American) who completed a newly developed global measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 93 publications
(148 reference statements)
2
57
1
Order By: Relevance
“…Notably, one primary source of confusion in the ER literature is the definition of ER goals, which have ranged from the motivation for regulating (e.g., managing one's impression on others; Eldesouky & English, ) to the act of regulating (Mauss, Cook, & Gross, ) or using specific tactics (e.g., McRae, Ciesielski, & Gross, ; Urry, ). Based on the extended process model (Gross, ), the act of regulating or using specific tactics is not in themselves ER goals because they are actions.…”
Section: A Process Model Perspectivementioning
confidence: 99%
See 4 more Smart Citations
“…Notably, one primary source of confusion in the ER literature is the definition of ER goals, which have ranged from the motivation for regulating (e.g., managing one's impression on others; Eldesouky & English, ) to the act of regulating (Mauss, Cook, & Gross, ) or using specific tactics (e.g., McRae, Ciesielski, & Gross, ; Urry, ). Based on the extended process model (Gross, ), the act of regulating or using specific tactics is not in themselves ER goals because they are actions.…”
Section: A Process Model Perspectivementioning
confidence: 99%
“…In the first half of this paper, we used the extended process model (Gross, ) to show that goals are central to all stages of ER. Recent studies indicate that individual difference factors (e.g., personality; Eldesouky & English, ) are important for predicting ER goals across various stages. Furthermore, studies have also shown that people differ in the extent to which they typically pursue various ER goals (e.g., English et al, ; Kalokerinos et al, ).…”
Section: An Individual Difference Approach To Er Goalsmentioning
confidence: 99%
See 3 more Smart Citations